A influência das debêntures na estrutura de capital das empresas de utilidade pública - Ribeiro, Irã Inácio (2018)
Studies on the capital structure show relevance even after more than 50 years of the seminal works of Modigliani and Miller (1958) due to the diversity of findings that appear in the academy. In view of this, this research aims to investigate the influence of debentures on the capital structure of public utility companies. The performance of other debt instruments, such as financing with development banks and bank financing, was also analyzed. In addition, the behavior of debt instruments in the capital structure was verified in an environment of economic and / or political crisis such as occurred in the world in 2010 and that experienced in Brazil in 2016. The sample is composed of 55 companies listed in Brazil (B3) in the period from 2010 to 2017. The data were collected in the notes to the financial statements of the companies, available on the B3 website. The research quantitatively analyzes the data through the Pearson correlation analysis of the mean difference test, of the linear regression with panel data. The same average was evidenced for two independent samples regarding total indebtedness, long-term indebtedness, profitability, leverage and liquidity. The regression with panel data showed a significant influence of the external environment on the financing decision among debt instruments; still through the panel it was found that, at the level of significance of 10%, the variable bank debts can be considered significant in the model and that debentures and subsidized debts were not presented as significant at the level of 1%, 5% and 10%. Leverage and liquidity have been shown to be significant in the total or long-term debt structure, which allows us to infer that companies have a good management when dealing with indebtedness. The results indicate that the public utility sector is aligned with the Pecking Order theory.